Multiple Primary Melanomas: A Common Occurrence in Western Sweden - Magdalena Claeson; Paul Holmström; Stefan Hallberg; Martin Gillstedt; Helena Gonzalez; Ann-Marie Wennberg; John Paoli (Medical Journals Sweden, 2017)
Patients diagnosed with a single primary cutaneous melanoma are at increased risk of developing multiple primary melanomas. The aim of this study is to describe the epidemiology of multiple primary melanomas (invasive and in situ) in Western Sweden. Data from the Swedish Melanoma Registry from 1990 to 2013 revealed that 898 patients (7.4%) developed 2,037 multiple primary lesions and 11,254 patients developed single lesions. The proportion of subsequent lesions that were melanoma in situ was 47%, compared with 26% of first melanomas (p < 0.0001).The median and mean time to diagnosis of a subsequent melanoma was 38 and 58 months (95% confidence interval (CI), 53-62 months). In total, 49% of subsequent melanomas were detected within 3 years. Patients and physicians should be aware of the high proportion of multiple primary melanomas in Western Sweden, especially during the first years of follow-up